A focused ethnographic study on grammar teaching practices across language subjects in schools - Kabel, Kristine; Christensen, Mette Vedsgaard; Brok, Lene Storgaard (Language, culture, and curriculum, 2022)
Studies exploring grammar teaching in first and foreign language subjects in Scandinavia are very rare. In this article, we present findings from a focused ethnographic study (Gramma3, 2018-2019) of grammar teaching practices in the three major first and foreign language subjects at lower-secondary level (age 13-15) in Denmark: Danish L1, English L2 and German L3, with data collected at seven schools. The dominance of traditional school grammar content in all three classrooms is one main finding. However, the approaches vary across the three subjects, mirrored also in different traditions and cultures for language learning within first and foreign language subjects. The co-existence of concurrent and even contradictory practices within each language subject is another main finding. Thus, the cross-curricular perspective of the present study leads to detailed findings suggesting new ways of understanding explicit grammar teaching in compulsory education. In this way, the study helps to shed light on an under-researched, yet key curricular content area in all three subjects, suggesting opportunities for cooperation between first and foreign language teachers. In turn, it contributes knowledge, which is valuable beyond the national context of the study, with the potential for comparative studies across borders.